Dams, Power, and the Politics of Ethiopia's Renaissance - Tom Lavers (Oxford University Press, 2024)
After more than a decade, Ethiopia is filling the Grand Ethiopian Renaissance Dam (GERD), a controversial dam with the potential to transform the hydrology and politics of the Nile Basin. The GERD is the culmination of a dam building boom carried out over three decades and a key pillar of the Ethiopian Peoples' Revolutionary Democratic Front's (EPRDF) efforts to bring about an Ethiopian 'Renaissance'. This book provides the first detailed examination of the domestic and international political dynamics that shaped Ethiopia's dam building, drawing on extensive primary research including more than a hundred interviews with politicians, technocrats, consultants, and donors. In doing so, the book reflects on Ethiopia's implications for broader debates about the role of the state in late development, the dynamics of twenty-first-century dam building, and the political economy of renewable energy transitions. A central argument of the book is that Ethiopia's dam building is symbolic of the successes and failures of the EPRDF's 'developmental state'. On the one hand, this dams' boom enhanced electricity generation capacity, while constituting a key element of the state infrastructure investment that turned Ethiopia into one of the world's fastest growing economies. On the other hand, a politically driven decision-making process undermined electricity planning, contributed to an unsustainable debt burden, and, ultimately, failed to provide reliable electricity access to key users. Following the EPRDF's collapse, the subsequent Prosperity Party government has taken steps away from the state-led development model of its predecessor, while labouring towards the final completion of the GERD.
Keywords: 320; Ethiopia; Nile; dams; political economy; Grand Ethiopian Renaissance Dam; electricity; hydropower; hydropolitics; Meles Zenawi; renewable energy transitions